2016
DOI: 10.1007/s10334-016-0589-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-gadolinium dynamic angiography of the neurovasculature using arterial spin labeling MRI: preliminary experience in children

Abstract: There is a steadily rising concern in adults and children over the potential effects of intracranial deposition of gadolinium. CINEMA is therefore a viable alternative in dynamic neurovascular imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…109 Both PASL and PCASL can be used for ASL-MRA. PASL with a Look-Locker readout has already proved its clinical usefulness in several studies 101,104,110,111 and is particularly good at visualizing the early inflow phase of the proximal arteries. However, vessel-selective PASL has some difficulties (see below), which makes PCASL a preferred option for vessel-selective MRA.…”
Section: Asl Angiography (Asl-mra)mentioning
confidence: 99%
“…109 Both PASL and PCASL can be used for ASL-MRA. PASL with a Look-Locker readout has already proved its clinical usefulness in several studies 101,104,110,111 and is particularly good at visualizing the early inflow phase of the proximal arteries. However, vessel-selective PASL has some difficulties (see below), which makes PCASL a preferred option for vessel-selective MRA.…”
Section: Asl Angiography (Asl-mra)mentioning
confidence: 99%
“…As an advanced ASL technique, contrast inherent inflow-enhanced multiphase angiography (CINEMA), introduced by Nakamura et al, provides the information on hemodynamics and structure of vessels in the target tissue without contrast agents [ 66 , 67 ]. The CINEMA technique requires PASL or pCASL tagging scheme and provides multi-timepoint data by varying the delay time interval between labeling and imaging at the slices of interest [ 68 , 69 ]. Iryo et al reported excellent agreement between CINEMA and digital subtraction angiography in visualizing the site of dural arteriovenous fistulas, including the fistula, the feeding arteries, and the draining veins [ 70 ].…”
Section: Clinical Applications Of 3d Tse Pcasl In the Head And Neckmentioning
confidence: 99%
“…Iryo et al reported excellent agreement between CINEMA and digital subtraction angiography in visualizing the site of dural arteriovenous fistulas, including the fistula, the feeding arteries, and the draining veins [ 70 ]. Hu et al successfully documented the intracranial AVM case that showed the nidus and the feeder arteries on CINEMA [ 68 ]. This technique can be applied to head and neck AVM, as shown in Figure 6 .…”
Section: Clinical Applications Of 3d Tse Pcasl In the Head And Neckmentioning
confidence: 99%
“…31 However, none of these three options should be considered to provide a perfect solution, which explains why PASL is still considered as one of preferred labeling techniques for dynamic ASL-MRA, and has proved its clinical usefulness in several previous clinical studies. [2][3][4][5] When imaging static 3D-MRA, however, the abovementioned dilemma is no longer relevant, and long pCASL labeling duration will ensures visualization of the complete arterial trees from proximal to distal vessels with adequate SNR. 16,25,27 Moreover, a hybrid of pCASL and PASL was suggested when using large FOV for imaging of extracranial carotid arteries, which could also minimize disappearance of the arterial signal due to fresh unlabeled blood flowing into the imaging volume.…”
Section: Labeling Module (General)mentioning
confidence: 99%
“…By taking advantage of this completely non-invasive feature, many studies were conducted to demonstrate that ASL can be an alternative technique for other more invasive techniques using X-ray and/or contrast agent. [1][2][3][4][5][6][7] This would especially be important for pediatric patients who need repetitive examinations to monitor disease progression. Whereas MR contrast agents used to be considered relatively safe, due to the established link between several linear gadolinium contrast agents and nephrogenic systemic fibrosis in patients with poor renal function as well as the recent observation of gadolinium deposition in the brain, 8 the European Medicines Agency decided to recommend the suspension of the use of four linear MR contrast agents and advise to limit the use of gadolinium based contrast agents to the lowest dose for diagnosis.…”
Section: Introductionmentioning
confidence: 99%